PELATIHAN EKSPRESI WAJAH POSITIF Untuk Mengurangi Depresi.itive Facial Expression Training to Decrease Depression. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Facial feedback hypothesis argues that (1) facial expression provides information about what emotion is being felt and (2) changes in facial expression cause the emotion itself. Based on that hypothesis, a positive facial expression training was designed. The training consisted of the facial muscle relaxation via tension-relaxation, the facial muscle relaxation via letting-go, and the facial expression training.The purpose of this study is to test the efficacy of positive facial expression training in reducing depression. Subjects were 19 Psychology students of 1994/1995. They were selected according to their Beck Depression Inventory (BDI) scores. They were divided into two groups: 10 subjects participated in the experimental group and 9 subjects participated in the waiting-list group as the control group. BDI was used as the main instrument to measure depression level. It was then compared to the Zung Self-Rating Depression Scale (ZSDS). Both instruments were administered four times: before the training, right after the training, one month as well as three months after the training.T-test analysis of BDI scores indicated that there was a significant difference in depression level between the experimental and the control groups after the training. The depression level of the experimental group was lower than the control group. The depression level of the experimental group was moderate before the training and was normal three months after the training.Analysis of ZSDS scores showed the same pattern of analysis of BDI scores, except that there was no significant difference in depression level between the two groups three months after the training.Therefore, it seemed that positive facial expression training was effective in reducing depression.